Clinical Decision Support Systems to Reduce Unnecessary Clostridioides difficile Testing Across Multiple Hospitals . (1st February 2022) - Rock, Clare; Abosi, Oluchi; Bleasdale, Susan; Colligan, Erin; Diekema, Daniel J; Dullabh, Prashila; Gurses, Ayse P; Heaney-Huls, Krysta; Jacob, Jesse T; Kandiah, Sheetal; Lama, Sonam; Leekha, Surbhi; et al.
Abstract: Background: Inappropriate Clostridioides difficile testing has adverse consequences for patients, hospitals, and public health. Computerized clinical decision support (CCDS) systems in the electronic health record (EHR) may reduce C. difficile test ordering; however, effectiveness of different approaches, ease of use, and best fit into healthcare providers' (HCP) workflow are not well understood. Methods: Nine academic and 6 community hospitals in the United States participated in this 2-year cohort study. CCDS (hard stop or soft stop) triggered when a duplicate C. difficile test order was attempted or if laxatives were recently received. The primary outcome was the difference in testing rates pre– and post–CCDS interventions, using incidence rate ratios (IRRs) and mixed-effect Poisson regression models. We performed qualitative evaluation (contextual inquiry, interviews, focus groups) based on a human factors model. We identified themes using a codebook with primary nodes and subnodes. Results: In 9 hospitals implementing hard-stop CCDS and 4 hospitals implementing soft-stop CCDS, C. difficile testing incidence rate (IR) reduction was 33% (95% confidence interval [CI]: 30%–36%) and 23% (95% CI: 21%–25%), respectively. Two hospitals implemented a non-EHR-based human intervention with IR reduction of 21% (95% CI: 15%–28%). HCPs reported generally favorable experiences and highlighted time efficiencies such as inclusion of the patient's most recent laxative administration on the CCDS. Organizational factors, including hierarchical cultures and communication between HCPs caring for the same patient, impact CCDS acceptance and integration. Conclusions: CCDS systems reduced unnecessary C. difficile testing and were perceived positively by HCPs when integrated into their workflow and when displaying relevant patient-specific information needed for decision making. Abstract : This 15-hospital, 2-year cohort, mixed-methods study found reduced Clostridioides difficile test incidence rates after computerized clinical decision support (CCDS) implementation. Healthcare providers' perceptions were positive when CCDS was integrated into their workflow and provided relevant patient-specific information.